Regulatory Compliance and Internal Control as Determinants of SME Financial Performance in Dubai: Implications for the Middle East - Siti Khodijah; Rachmat Agus Santoso (Manunggal Halim Jaya, 2026)
Small and Medium Enterprises (SMEs) play a crucial role in supporting economic diversification in Dubai and the broader Middle East region. However, despite their strategic importance, SMEs remain vulnerable to financial instability due to weak governance structures, particularly in regulatory compliance and internal control practices. This study aims to examine the effect of regulatory compliance and internal control on SME financial performance in Dubai. This research adopts a quantitative approach using primary data collected through structured questionnaires distributed to financial staff of SMEs. A total of 69 valid responses were obtained, representing SMEs across various sectors. Data were analyzed using multiple linear regression with SPSS. The results indicate that regulatory compliance has a significant positive effect on SME financial performance, while internal control also positively contributes to improving financial outcomes. These findings suggest that stronger governance mechanisms can enhance financial sustainability and operational efficiency. This study contributes to the literature by providing empirical evidence from a Middle Eastern context and offers practical implications for SME managers and policymakers to strengthen governance frameworks.